Foucault reader of Nietzsche? Exegesis or interpretation - ALZURU APONTE , Jonatan (Utopía y Praxis Latinoamericana, 2025)
Abstract: In this paper we pose as a problem: what does it mean to question the reading of Nietzsche in Foucault? The backbone of the article is the distinction between exegesis and interpretation. Both Nietzsche and Foucault will be used to account for the distinction. Such an exercise will lead us to establish our position on the matter.